Encyclopedia of Christianity in the United States - Kurian, George Thomas; Lamport, Mark A.; Marty, Martin E., 1928-2025 (Lanham, Maryland : Rowman & Littlefield, 2016)
From the founding fathers through the present, Christianity has exercised powerful influence in the United States from its role in shaping politics and social institutions to its hand in inspiring art and culture. The Encyclopedia of Christianity in the United States outlines the myriad roles Christianity has played and continues to play. This masterful five-volume reference work includes biographies of all major figures in the Christian church in the U.S., influential religious documents and Supreme Court decisions, information on theology and theologians, denominations, faith-based organizations, immigration, art from decorative arts and film to music and literature, evangelism and crusades, the significant role of women, racial issues, civil religion, and more.--Publisher description.
Volume 1. A-C -- volume 2. C-G -- volume 3. H-M -- volume 4. N-S -- volume 5. S-Z.
Includes bibliographical references and indexes.
Keywords: Christianity -- United States -- Encyclopedias